PENERAPAN FATWA DEWAN SYARIAH NASIONAL NO 17 DAN N0 43 PADA SISTEM MURABAHAH: Studi kasus pada Koperasi Syariah Huwaiza di Pancoran Mas Depok - Administrator, Journal (Al Mashalih - Journal of Islamic Law, 2018)
This study aims to determine whether the technical implementation of sanctions against customers capable of procrastinating payments on Shari'ah Huwaiza Cooperative is in accordance with the fatwa of the Council of Sharia Indonesia Ulema Council, as well as know what are the losses that result in financial cooperatives. The study used descriptive analysis as a reference material so that we can convey our research results by describing in the form of writing taken from interviews and data. The researchers found that sanctions in the form of infak were imposed on customers who defaulted, and shariah financial institutions will give a grace period for those who are late in paying their obligations. And will do the rescheduling against them with the agreed time. The system of control they are doing is the approach to the community to find out what makes them late in payments. And by way of coming to their house intensively, there is also a warning letter gradually ranging from warnings to the decision to sell collateral, or by building a new contract.